Establishing a Performance Management Framework for Government - Diamond, Jack (IMF Working Papers; Working Paper, 2005)
Based on the experience of budget management reforms that have been introduced over the last two decades in a large number of member countries of the Organization for Economic Cooperation and Development (OECD) it is not uncommon to find emerging market economies moving toward performance-based budgeting where measures of performance play a key role. While it might be tempting for middle income countries to press forward to adopt a full-blown outputs and outcomes framework, there are some risks in the move. Such a change in orientation is only possible once managers have had adequate experience in refining the definition of programs and their objectives, and on this basis developing a comprehensive system of performance measurement. It is argued in this paper that to develop a comprehensive performance measurement system requires resolving a number of issues involved in clearly defining how to measure "performance" as well as overcoming a number of technical issues in the design and use of measures of that "performance." However, perhaps the most critical step is introducing a system whereby performance information can influence resource allocation decisions, id est, establishing a performance management system. Based on international experience, this paper reviews each of these hurdles in moving toward a performance management framework.